2020
DOI: 10.1002/1873-3468.13893
|View full text |Cite
|
Sign up to set email alerts
|

Irc3 is a monomeric DNA branch point‐binding helicase in mitochondria of the yeast Saccharomyces cerevisiae

Abstract: Irc3 is a superfamily II DNA helicase required for the maintenance of mitochondrial DNA stability in Saccharomyces cerevisiae. Here, we show that recombinant Irc3 is a monomeric protein and that it can form a binary complex with forked DNA. The catalytically active enzyme is a monomer as no positive cooperativity of ATP hydrolysis or DNA unwinding can be detected. Interestingly, we find that Irc3 prefers to unwind the nascent lagging strand at a replication fork. Using DNase I footprinting, we demonstrate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…It remains unclear how Irc3 positions itself on branched DNA and several options can be considered. Irc3 consists of a helicase motor translocating on DNA and our data suggest that the protein makes stronger contacts with the DNA strand that has 3’-5’ polarity in the parental duplex of the forked substrate [16,33]. It is possible that the helicase core domain positions on the parental duplex similarly to what has been suggested for the RecG helicase of E. coli [34].…”
Section: Discussionmentioning
confidence: 68%
“…It remains unclear how Irc3 positions itself on branched DNA and several options can be considered. Irc3 consists of a helicase motor translocating on DNA and our data suggest that the protein makes stronger contacts with the DNA strand that has 3’-5’ polarity in the parental duplex of the forked substrate [16,33]. It is possible that the helicase core domain positions on the parental duplex similarly to what has been suggested for the RecG helicase of E. coli [34].…”
Section: Discussionmentioning
confidence: 68%
“…Deletion of IRC3 has previously been reported to accumulate double stranded mitochondrial DNA breaks (Sedman et al, 2014). ATPase activity of Irc3 protein is essential in vivo and in vitro is stimulated by DNA molecules especially those mimicking recombination intermediates (Gaidutsik, Sedman et al, 2016, Piljukov et al, 2020, Sedman et al, 2014). Here in we have clearly shown that IRC3 is required for mitochondrial translation in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…MSS116 has been shown to play a role in transcription, mRNA splicing and translation (De Silva, Poliquin et al, 2017, Halls, Mohr et al, 2007, Markov, Wojtas et al, 2014, Zingler, Solem et al, 2010), while MRH4 and SUV3 are known to be involved in ribosome biogenesis and RNA editing/turnover respectively (De Silva, Fontanesi et al, 2013, Dziembowski, Piwowarski et al, 2003, Malecki, Jedrzejczak et al, 2007, Turk & Caprara, 2010). The fourth mitochondrial helicase, IRC3 has been implicated in mtDNA recombination and repair (Piljukov, Garber et al, 2020, Sedman, Gaidutsik et al, 2014). However, these studies were carried out in strains deleted for IRC3 , in which loss of mtDNA could be either due to a direct role of Irc3 in regulating mtDNA recombination/repair or due to an indirect consequence of Irc3’s role in an essential process involving RNA molecules such as transcription and translation.…”
Section: Introductionmentioning
confidence: 99%